2012
DOI: 10.1159/000341999
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the Cognitive Effects of Levodopa versus Dopamine Agonists in a Neurocomputational Model of Learning in Parkinson’s Disease

Abstract: Background/Aims: Levodopa and dopamine agonists have different effects on the motor, cognitive, and psychiatric aspects of Parkinson’s disease (PD). Methods: Using a computational model of basal ganglia (BG) and prefrontal cortex (PFC) dopamine, we provide a theoretical synthesis of the dissociable effects of these dopaminergic medications on brain and cognition. Our model incorporates the findings that levodopa is converted by dopamine cells into dopamine, and thus activates prefrontal and striatal D1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 147 publications
2
22
0
Order By: Relevance
“…Some studies showed that learning and retention of memory, required for optimal response choice, are significantly reliant on dopamine in Alzheimer's Disease [29,30]. However, some studies found that dopamine impairs or have no effect on, stimulus-response learning and working memory in Parkinsonism or MHE [31,32,33], similarly in our present study we displayed that overproduction of DA is a feature for memory impairment in MHE. Brodskii VY et al reported that dopamine disorganizes the rhythm of protein synthesis in hepatocytes in vitro and in vivo [34,35], indicating the relationship of elevation of DA with liver cirrhosis on the other side.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies showed that learning and retention of memory, required for optimal response choice, are significantly reliant on dopamine in Alzheimer's Disease [29,30]. However, some studies found that dopamine impairs or have no effect on, stimulus-response learning and working memory in Parkinsonism or MHE [31,32,33], similarly in our present study we displayed that overproduction of DA is a feature for memory impairment in MHE. Brodskii VY et al reported that dopamine disorganizes the rhythm of protein synthesis in hepatocytes in vitro and in vivo [34,35], indicating the relationship of elevation of DA with liver cirrhosis on the other side.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, although our findings in the present study must primarily be conceived as purely in vitro model data, they may also have some bearing in understanding liver cirrhosis complicated with MHE, when a disruption of the BBB is prone to occur. Numerous studies describe the specific effects of DA manipulations on learning and how low doses of DA facilitate cognitive abilities [25][26][27]; however, some studies (including our studies) show that overproduction of DA impairs learning and working memory [6][7][8][9]28]. Chronic HE patients exhibit abnormalities in their dopaminergic systems, including an increase in the brain content of DA metabolites [29] and increased turnover of DA [30].…”
Section: Discussionmentioning
confidence: 71%
“…However, our results demonstrate a significant impairment in recognition of non-verbal vocal burst representing positive emotions, but not for negative ones in the medicated PD patients tested before their DBS procedures. The reported results of PD emotion-recognition studies are mixed (Kan et al, 2002; Assogna et al, 2010; Moustafa et al, 2013). The discrepancies between the studies may be related to the stimulation modality (e.g., visual vs. auditory; Kan et al, 2002), the type of dopaminergic therapy (e.g., Levodopa vs. dopamine agonists; Moustafa et al, 2013), the intensity of presented emotions (Assogna et al, 2010), and the testing conditions (i.e., high patient stress and anxiety at the day before surgery in our setup).…”
Section: Discussionmentioning
confidence: 99%